The Syrian olive oil sector: a strategic appraisal [printed version also available in Arabic] - Brillante G.; Conto F.; Dragotta A. (Syrian national strategic plan for olive oil quality : final report, 2007)
Two short missions have been carried out at the end of the project implementation phase in order to integrate the technical advice provided by the whole project expertise in the field of training, technology transfer, institutional capacity building and technical assistance carried out during 2 and a half years of implementation, to a more global and integrated evaluation through a strategic appraisal that includes the Syrian agricultural policy, olive oil trading and the socio economic related scenarios. On the base of the pluri-annual experience of the Apulia organizational olive oil producers' realities and taking the opportunity of the results and answers given by the Project for the Technical assistance for the Improvement of olive oil quality in Syria combined expertise, the main guidelines for the future integrated approach for the Syrian olive oil sector have been drawn through SWOT analyses based on the technical lacks up to the needs of a properly driving for the trading and exporting private sector and its potential to face the new challenges of the Mediterranean and international quality olive oil demand. Gradual implementation of the technical advice described in this strategic plan together with the creation of Producers' associations and the improvement of the monitoring system at custom level for the olive oil quantities and quality exported abroad represent some of the mandatory priorities to be achieved as soon as possible.